2012
DOI: 10.1212/wnl.0b013e31825fdec7
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum vitamin D levels are associated with a higher relapse risk in multiple sclerosis

Abstract: Our finding that higher vitamin D levels are associated with decreased exacerbation risk in relapsing-remitting MS suggests a beneficial effect of vitamin D on disease course in MS. However, the possibility of reverse causality cannot be ruled out completely. Randomized intervention studies are therefore needed to investigate the effect of vitamin D supplementation in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(134 citation statements)
references
References 30 publications
(18 reference statements)
9
120
0
3
Order By: Relevance
“…In our study we found that 65% of patients had abnormal low vitamin D level, also many studies conducted by Smolders J. and his colleagues [15], Correale and his colleagues [16], Van Der Mei and his colleagues [17] and lastly Runia T.F. and his colleagues [18], who all found that hypoviatminosis D highly associated with MS patients.…”
Section: Discussionsupporting
confidence: 85%
“…In our study we found that 65% of patients had abnormal low vitamin D level, also many studies conducted by Smolders J. and his colleagues [15], Correale and his colleagues [16], Van Der Mei and his colleagues [17] and lastly Runia T.F. and his colleagues [18], who all found that hypoviatminosis D highly associated with MS patients.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast to these inconclusive small controlled studies, several recent association studies found a significant relationship between the vitamin D status and the relapse rate in patients with RRMS [Smolders et al 2008b;Runia et al 2012], with possible variable positive or negative interactions with IFNβ depending upon the vitamin D serum level, higher or lower than 50 nmol/liter respectively [Stewart et al 2012]. In another recent association study, preliminary results provided evidence that low serum 25-OH-D levels are an important risk factor for conversion from CIS to MS, suggesting that vitamin D supplementation in combination with IFNβ-1b may improve outcomes in CIS [Ascherio et al 2012b].…”
Section: Relapsesmentioning
confidence: 89%
“…In patients with MS living in temperate and Nordic countries, as in the general populations of these countries, vitamin D insufficiency is widespread, whatever the cutoff (50 or 75 nmol/ liter) for the lower limit of the 25-OH-D serum level ( Figure 3): indeed, as early as the earliest stages of the disease, that is, in patients with clinically isolated syndrome (CIS) or with RRMS, average serum levels are between 42 and 74 nmol/ liter, depending on the studies and the seasons, with a general mean close to 60 nmol/liter [SoiluHänninen et al 2005[SoiluHänninen et al , 2012Smolders et al 2008b;Hiremath et al 2009;Kragt et al 2009;Mowry et al 2010;Pierrot-Deseilligny andSouberbielle, 2010, 2012;Simpson et al 2010;Banwell et al 2011;Dabbaghmanesh and Yousefipour, 2011;Lonergan et al 2011;Neau et al 2011;Steffensen et al 2011;Yildiz et al 2011; Bäärnhielm Kampman et al 2012;Kirbas et al 2012;Løken-Amsrud et al 2012;Moen et al 2012;Runia et al 2012;SoiluHänninen et al 2012;Šaltyte . Benth et al 2012;Triantafyllou et al 2012] (Table 1).…”
Section: Vitamin D Requirements and Insufficiencymentioning
confidence: 99%
“…In the recent years, this seasonal relationship is postulated to be associated with serum vitamin D levels (23). Data coming from relevant studies show that lower vitamin D levels are associated with more frequent relapses (24,25). It has been demonstrated that previously accused physical trauma, vaccinations, and epidural anesthesia do not have relapse triggering effects.…”
Section: The Definition and Features Of Relapsementioning
confidence: 99%